A new method of parameter estimation for sinusoidal frequency modulated continuous wave signal - Xiaopeng NIE; Zucheng SHEN; Xiaofeng WANG; Chunyu WANG (Dianxin kexue)
A new method of modulation parameter estimation was proposed to process the sinusoidal frequency modulated continuous wave signal intercepted by electronic reconnaissance.Firstly,based on the periodicity of signal modulation function,the modulated frequency was estimated using autocorrelation function.And then,the frequency modulation curve was extracted and revised based on rearranging spectrogram.Finally,the carrier frequency,the modulation exponent and the initial phase were estimated by the frequency modulation curve.The simulation experiment results show that the proposed method does not require prior knowledge,and the mean square error of each modulation parameter can reach -25 dB by using this method when SNR is -5 dB.